Students' views on student-teacher relationship: A questionnaire-based study - Khalid A Bin Abdulrahman (Wolters Kluwer Medknow Publications, 2007)
Aim: The aim of this study is to assess students' views on student-teacher relationship and its effect on academic grades. Methods: The present cross-sectional study was conducted in the College of Medicine, King Saud University, Riyadh, in 2005. The questionnaires were distributed to 420 students during the examination period in order to obtain a full response. It consisted of items on different aspects of student-teacher relationship for which the responses were measured on a 4-point scale. The response rate was about 83%. Results: The current relationship between the student and the teacher was evaluated as very good and good by 61% of the study sample. The responses were associated with their grades as (X [2] =6.25, p=0.012). Eighty-four point one percent of students with higher and above average grades felt that expulsion from class was an appropriate means of controlling the class. Also (78.2%) students felt that the teachers treated them with respect, and their responses were significantly associated with their grades (X [2] =11.8, p=0.003). Eight-four percent of the students with higher and above average grades strongly agreed that teacher's performance was affected by students' attendance or absence and the responses were significantly associated with their grades (X [2] =4.35, p=0.037). The responses to most of the items by the students were independent of their grades. Conclusion: This study concludes that student-teacher relationship was good in a medical school and the views of students on this relationship were independent with their academic grades. Further study which includes from 1 st year to 5th year undergraduate students is required to give a broader view of student-teacher relationship in a medical school.